Racial Disparities in 30-Day Readmission Rates After Elective Spine Surgery: A Single Institutional Experience. Issue 21 (1st November 2016) - Adogwa, Owoicho; Elsamadicy, Aladine A.; Mehta, Ankit I.; Cheng, Joseph; Bagley, Carlos A.; Karikari, Isaac O.
Abstract : Study Design: Retrospective cohort review. Objective: The aim of this study is to investigate whether patient race is an independent predictor of unplanned 30-day hospital readmission after elective spine surgery. Summary of Background Data: Racial disparities are known to exist for many aspects of surgical care. However, it is unknown if disparities exist in 30-day readmissions after elective spine surgery, an area that is becoming a prime focus for clinical leaders and policymakers. Methods: Records of 600 patients undergoing elective spine surgery at a major academic medical center were reviewed. We identified all unplanned readmissions within 30 days of discharge. Unplanned readmissions were defined to have occurred as a result of either a surgical or a nonsurgical complication. Patient's records were reviewed to determine the cause of readmission and the length of hospital stay. The main outcome measure was risk-adjusted odds of all-cause 30-day readmission. We used multivariate logistic regression to determine if Black patients had an increased likelihood of 30-day readmission compared with White patients. Results: Baseline characteristics were similar between both groups. Black patients had higher readmission rates than White patients (10.56% vs. 7.86%, P  = 0.04). In a univariate analysis, race, body mass index, sex, patient age, smoking, diabetes, and fusion levels were associated with increased 30-day readmission rates. However, in a multivariate logistic regression model, race was an independent predictor of 30-day readmission after elective spine surgery. In addition, no significant differences in baseline, 1-year and 2-year patient reported outcomes measures were observed between both groups. Conclusion: This study suggests that Black patients are more likely to be readmitted within 30-days of discharge after elective spine surgery. Efforts at reducing disparities should focus not only on race-based measures but also effective post discharge care. Level of Evidence: 3